(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Nowadays, the energy transition from fossil fuels to renewable energy sources is at a crucial point. Indeed, a plethora of technologies is available for exploiting a number of renewable sources. Among the various sources, sea wave energy is widely recognized for its energetic potential. Several wave energy converters have been proposed, studied, and tested. In particular, the Oscillating Water Column (OWC) technology stands out as one of the most developed and reliable in terms of resistance to wave loads and energy conversion efficiency. Its working principle relies on the oscillation of a water column confined within a chamber, driven by the wave motion transmitted through an opening at the base. This oscillatory motion compresses and expands the air pocket above it, by creating a bidirectional airflow through an orifice. By installing a turbine, this airflow can be harnessed for energy production purposes. The main obstacle to large-scale development is the current high levelized cost of energy, which is not competitive vis-à-vis the ones of other energy converters. In this context, optimizing energy production through in-depth analysis could reduce the cost of the energy generated. This study analyses the energy – wise performance of multi-chamber OWCs embedded in circular platforms. The critical feature of the device is that the OWC chambers are distributed on the external side of the platform, therefore they span a limited portion of the circular domain and have a limited angular width. Specifically, the article considers two devices: one device comprising a cylindrical structure with two chambers; and another one with three chambers. In both cases, the array occupies the entire full circle, and the chambers have identical angular width. A semi-analytical solution consistent with the linear potential flow theory is formulated to solve the associated diffraction and radiation problems. The solution is developed by a domain decomposition technique accommodating the representation of the velocity potentials pertaining to each sub-domain via eigenfunction expansions, whose unknown coefficients are determined through a matching technique enforcing the continuity of pressure and of velocity along two contiguous sub-domains. In this context, a linear Power Take-Off is considered. The article investigates the characteristics of excitation volume flow rate, radiation damping, added mass, capture width, and surface elevation inside the chambers. Each result is compared to the case of a single-chamber cylindrical device to assess the advantages and disadvantages of the two configurations with a state-of-the-art OWC configuration.